Add Value Through Internal Audit to An Organisation - Saxena, Preeti (Journal of Commerce and Trade, 2020)
Internal auditing is an independent management function that entails a continuous and critical evaluation of an entity's operations with the goal of suggesting improvements and adding value to and strengthening the entity's overall governance mechanism, including its strategic risk management and internal control system. The golden principles set forth in the code of ethics for internal government auditors are integrity, objectivity, competence, confidentiality, and independence. As mentioned above, internal audit is an independent evaluation function established within an organization to inspect and evaluate its activities as a service to the organization. Therefore, the goal of internal audit is to assist organization members to effectively perform their duties. To this end, internal audit provides them with analysis, evaluation, recommen-dations, suggestions and information related to the review activities. The objectives of the audit include promoting effective control at a reasonable cost.